Evaluation of Information Systems in Public Libraries Using the Delone & Mclean Model - Ahmad Tamrin, Nur Ain Kamilah (Edulib, 2021)
While many researchers have investigated the adoption and use of information systems in academic libraries, one section has not been thoroughly researched, particularly in public libraries that have adopted the use of information systems. Now public libraries have started to use or subscribe to any existing information system in line with the needs of the local community. The purpose of this paper is to identify and obtain information regarding the suitability or achievement of information system services used in public libraries using the Delone and Mclean information system success model. The method of data collection is to use an online survey questionnaire to obtain primary sources from the general public around. The findings of the investigation showed that the system quality, information quality, service quality, usage, user satisfaction and net benefits showed significantly good and satisfactory results and this further indicated that the information system service in public libraries was achieved. The results can help librarians to improve the information systems used so that their information system services can be improved to the maximum stage.